Strategies of Polite Language in Pramono's Discourse on the Role of Santri in Maintaining National Morals on Antaranews.com - Isnaeni Isnaeni; Sry Wahyuni (Edumaspul: Jurnal Pendidikan, 2025)
This study discusses the forms of language politeness strategies that appear in the discourse of the Governor of DKI Jakarta, Pramono Anung Wibowo, regarding the role of santri as guardians of national morality as published on Antaranews.com. This study uses a pragmatic approach with Brown and Levinson's (1987) politeness theory, which highlights four main strategies, namely positive politeness, negative politeness, bald on record, and off record. This research was conducted using a qualitative descriptive method through analysis of data in the form of excerpts from Pramono's statements in news texts and the context of his speech. The results of the analysis show that Pramono mostly uses positive and negative politeness strategies to build an image as a polite leader who respects and is close to the santri community. The use of these strategies demonstrates Pramono's efforts to strengthen social relations between the government and the santri community, while also emphasizing Islamic ethical and moral values in public communication. Thus, the discourse presented by Pramono reflects ethical political communication practices rooted in politeness and national character.